Measure the Readiness of Food MSME System to Save Food System through the Market System During Pandemic COVID-19 (Case Study: SME Snack Food Cluster in Temanggung Regency) - Surya Tri Esthi Wira Hutama; Muhammad Indra Hadi; Holi Bina Wijaya (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
The COVID-19 pandemic has had an impact on the global economy, especially for businesses. One of the business actors and sectors that are most directly affected are the MSMEs (Micro, Small, and Medium Enterprises) actors. MSMEs have a vital role in this situation because they can directly affect local villages' food systems and economic movement. One of them is the production of snacks, namely the business activity of processing raw materials (commodities) into food products up to the marketing stage. Snack SMEs are expected to adapt during a pandemic, considering that food is a crucial need quickly. The location studied in this study is Temanggung Regency as a district with high local potential and running many micro and small businesses such as snack food MSMEs in Central Java, Indonesia. This research aims to measure the readiness and adaptation so that snack MSMEs can survive. The analysis method is carried out with a market system framework approach starting from raw materials, processing, and marketing stages. The data of this study were obtained from primary data collected through interviews and questionnaires of MSME cluster actors in Temanggung District. This study indicates that the readiness of business actors with a new market system framework through the use of technology in SME snacks makes business actors survive in the era of the COVID19 pandemic.